Sul Manifesto di Bottiroli (Comparatismi, 2019)
L’autore propone alcune riflessioni in dialogo con Return to Literature. A Manifesto in Favour of Theory and against Methodologically Reactionary Studies di Giovanni Bottiroli.The author presents some reflections in dialogue with Giovanni Bottiroli’s Return to Literature. A Manifesto in Favour of Theory and against Methodologically Reactionary Studies.